2022
DOI: 10.1088/1361-6463/ac8560
|View full text |Cite
|
Sign up to set email alerts
|

Insulation degradation affected by micron metal particles attached on epoxy surface: charge accumulation and flashover voltage

Abstract: The micron metal particles are inevitable produced in long-term operation condition of HVDC SF6 insulated apparatus, which could frequently cause the surface discharge. Degradation of long-term surface discharge will be a severe threat to the insulation strength. Aiming at this problem, the surface charge accumulation and flashover voltage of epoxy itself before and after discharge degradation by particles were compared in this paper. The composition after degradation was measured by EDS and FTIR. The microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Epoxy resin/Al 2 O 3 composite insulators are the weak points in UHV gas insulation equipment [2][3][4]. With the increase in voltage level and transmission capacity of DC transmission systems, the electrical, thermal, and mechanical stress inside the equipment gradually increases, and the problems of thermal stability, aging performance, and surface insulation performance of epoxy resin/Al 2 O 3 composite materials are prominent [5,6]. Si 3 N 4 ceramics have great potential in the field of gas insulation due to their excellent insulation performance, mechanical performance, thermal stability, and chemical stability [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resin/Al 2 O 3 composite insulators are the weak points in UHV gas insulation equipment [2][3][4]. With the increase in voltage level and transmission capacity of DC transmission systems, the electrical, thermal, and mechanical stress inside the equipment gradually increases, and the problems of thermal stability, aging performance, and surface insulation performance of epoxy resin/Al 2 O 3 composite materials are prominent [5,6]. Si 3 N 4 ceramics have great potential in the field of gas insulation due to their excellent insulation performance, mechanical performance, thermal stability, and chemical stability [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al carried out repeated discharges on epoxy surfaces in SF 6 and found that the degradation caused by the discharge decomposed the epoxy surface and increased the proportion of O element, but multiple discharges led to an increase in surface fluorination products [9]. Yang et al found that when there are particles attached to the epoxy surface, the discharge of the particles will destroy the covalent bonds on the surface during the long-term degradation process, resulting in a decrease in the trap energy level [10]. Wen et al carried out the effect of degradation on the microstructure of materials due to AC discharge, and their proposed epoxy cleavage products include H 2 O and CH 4 , and their formation mechanisms include reactions involving free radicals, demethylation reactions, etc [11].…”
Section: Introductionmentioning
confidence: 99%
“…FGM is a kind of novel composite material, containing a spatial variation in composition and/or structure for the specific purpose of controlling variations in thermal, mechanical, or functional properties [6]. According to Maxwell's theory, the electric field distribution under an alternating current (AC) voltage depends on the permittivity distribution of involved materials, while that under the DC voltage is determined by the conductivity of materials [7]. Therefore, the electric field distributions along the surface of insulators can be controlled by the spatial gradient variation of dielectric parameters (permittivity and conductivity).…”
Section: Introductionmentioning
confidence: 99%